Carrier concentration modeling of bilayer graphene - Saeidmanesh, Mehdi (2012)
In this paper, the carrier concentration for bilayer graphene is modelled. The effect of an applied interlayer voltage V on the bandgap and carrier concentration is analysed using a new analytical approach. We begin by modelling of the density of states followed by carrier concentration as a function of V. It is found that as V increases, carrier concentration and the bandgap also increase.